White tea drink (Camellia sinensis) improves endurance and body weight maintenance of rats - Mahmud Aditya Rifqi; Stefania Widya Setyaningtyas; Qonita Rachmah (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - White tea is an unfermented tea made from young shoots of Camellia sinensis protected from sunlight to avoid polyphenol degradation. White tea contains a high level of polyphenolic compounds known as catechins. Several types of evidence have suggested that tea consumption has benefits in body weight and endurance maintenance. This study was designed to evaluate the effect of white tea on body weight and endurance of animal models. Design/methodology/approach - This research was an intervention design using 20 Wistar white rats (Rattus Norvegicus) in body weight between 150 and 200 g. The rats were randomized into four groups, three groups receiving white tea drink (WTD) with different doses and the other group receiving plain water in equal volume as a control group for four weeks. The forced swim test (FST) was done to measure their struggling capacity, and digital bodyweight to measure the weight. Findings - Intervention (WTD Groups and Control) caused weight gain among except G3 with the highest doses of white tea. The result showed that WTD intake in G3 had a significant difference (p < 0.05) on body weight gain compared to control. The authors found that WTD in a specific dose (G3: 0.22 mg) tends to maintain the body weight of animals (219.2 ± 41.96; 212.6 ± 46.90, respectively), while other doses caused weight gain. WTD also significantly increased the swimming and struggling capacity of rats that represented improvements the endurance along with the test. There was a statistically significant difference in endurance among all groups (p < 0.05). Research limitations/implications - The results of this study can be followed as human intervention research as an input for nutritionists and sports scientists to explore the beneficial effect of white tea. Practical implications - The results of this study can be followed as human intervention research as an input for nutritionists and sports scientists to explore the beneficial effect of white tea. Originality/value - This study adds more evidence and information about the advantages of white tea as potential beverages in future healthy lifestyles.